PENGARUH KEPEMILIKAN SAHAM EKSEKUTIF, KOMPENSASI EKSEKUTIF, DAN KOMISARIS INDEPENDEN TERHADAP TAX AVOIDANCE - Ellena Nabilah Nur Alisha Ansar, (2021)
This study aims to determine the effect of executive share ownership, executive compensation and independent commissioners on tax avoidance. This study uses manufacturing companies listed on the Indonesia Stock Echange (BEI) for the period 2015-2019. The sampling technique used was purposive sampling method. The sample used in this study were 52 manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2015-2019 period. Hypothesis testing is done using mulitple linear regression analysis with the SPSS 26 program and a significance value of 5%. The results of this study indicate that : (1) Executive share ownership has no significant effect on tax avoidance, (2) Executive compensation has significant positive effect on tax avoidance, (3) Independent commissioners have no significant effect on tax avoidance, (4) Executive share ownership, executive compensation, and independent commissioners are only able to explain tax avoidance by 3,1%.